Beyond borders circular economy and marketing a multi-national investigation - Jan, Muhammad Tahir (MASHREQ INTERNATIONAL FOR BOOKS SDN BHD, 2024)
In today's world, the pressing need for environmental sustainability has led to the emergence of "The Circular Economy" as a transformative approach to production, consumption, and disposal. Aligned with the United Nations Sustainable Development Goals, this philosophy aims to reshape global prosperity while preserving the planet for future generations.